A combination of self-potential and Schlumberger VES measurements for subsurface layering investigations - ΠΑΠΑΘΕΟΦΑΝΟΥΣ, Γ.; ΣΚΙΑΝΗΣ, Γ.; ΠΑΠΑΔΟΠΟΥΛΟΣ, Τ.; ΝΙΚΟΛΑΟΥ, Σ. (Bulletin of the Geological Society of Greece, 2001)
Self-potential (SP) anomalies can be useful in locating discontinuities in underground structure where water-flow occurs, but their interpretation is sometimes ambiguous. This paper was initiated by an effort to form a relatively accurate picture of the subsurface structure by combining SP measurements with Schlumberger soundings. The data employed come from a 1996 series of measurements carried out for a hydrogeological study near the village of Pigi of Rethimnon province in Crete Island. Data from 8 vertical electrical soundings (VES) were first used to determine the structure and possible lateral variations in the subsurface. For this, two parallel geoelectrical cross-sections were drawn, by considering simplified models. One of these cross-sections was employed in reducing the smoothed SP data to a homogeneous medium. This was necessary in order to make use of an interpretation algorithm (SPIN). The program is based on Fitterman's model of a dipping polarized plane for calculating SP anomalies, when the anomalies are generated by water flow along a boundary between rocks with different cross-coupling properties, that is through thermoelectrical or electrokinetical mechanism. Two major SP anomalies were observed, which suggest water presence. The interpretation algorithm led to the model parameters of the two sources, that reproduced accurately the anomalies. Their positions are in good agreement with those of the lateral discontinuities revealed by VES results. On examining the geological map of the area, we concluded that one of the sources might well be the prolongation of a fault disappearing about 2km from the SP line, while a second fault could explain slight lateral differences between the two geoelectrical crosssections.